Dakwah tekstual & kontekstual. Peran dan fungsinya dalam pemberdayaan ekonomi umat - PUTEH, M Jakfar (AK. Group, 2006)
Dakwah tekstual & konstektual. Peran dan fungsinya dalam pemberdayaan ekonomi ...